2007
DOI: 10.1038/sj.onc.1210622
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' tumor protein 1: an early target of progestin regulation in T-47D breast cancer cells that modulates proliferation and differentiation

Abstract: Progesterone regulates the proliferation and differentiation of normal mammary epithelium. In breast cancer cells, progesterone and its synthetic analogs, progestins, induce long-term growth inhibition and differentiation. However, the mechanisms responsible are not fully understood. When T-47D breast cancer cells were treated with the synthetic progestin ORG 2058 (16a-ethoxy-21-hydroxy-19-norpregn-4-en-3,20-dione), all isoforms of Wilms' tumor protein 1 (Wt1) mRNA and protein were rapidly downregulated. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
2
13
1
Order By: Relevance
“…So far the exact role of WT1 in the female reproductive system is not fully understood. In healthy endometrium progesterone induces WT1 isoforms which in turn leads to the differentiation into decidua [64], while in breast cancer cells progesterone analogs reduce WT1 expression thereby inducing differentiation [65]. As we examined mammary tissue without overt pathologic alterations, the observed induction of WT1 might point to premature differentiation, which is supported by the findings of our whole mount analyses showing smaller mammary glands and by the fact that an early increase in progesterone is detected in IUGR animals at day 28.…”
Section: Discussionsupporting
confidence: 61%
“…So far the exact role of WT1 in the female reproductive system is not fully understood. In healthy endometrium progesterone induces WT1 isoforms which in turn leads to the differentiation into decidua [64], while in breast cancer cells progesterone analogs reduce WT1 expression thereby inducing differentiation [65]. As we examined mammary tissue without overt pathologic alterations, the observed induction of WT1 might point to premature differentiation, which is supported by the findings of our whole mount analyses showing smaller mammary glands and by the fact that an early increase in progesterone is detected in IUGR animals at day 28.…”
Section: Discussionsupporting
confidence: 61%
“…Though Miyoshi et al (18) found that the prognosis of patients with high WT1 expression was significantly worse than that in patients with low WT1 expression, Camcı et al failed to confirm this finding in a later study (23). In the present study, we concluded that WT1 mRNA high expression predicted poor prognosis of breast cancer patients when using 3.1 as cutoff value, which might be due to the facts that WT1 could promote proliferation, invasion, migration, response to hypoxia and drug resistance of cancer cells (19)(20)(21)(22)35,37,38).…”
Section: Discussioncontrasting
confidence: 50%
“…Miyoshi et al found that WT1 mRNA significantly correlated with the poor prognosis of breast cancer (18). In addition, WT1 could promote the proliferation and restrain the apoptosis of breast cancer cells (19)(20)(21), all of which indicate that WT1 might serve as an oncogene in breast cancer. Therefore, it is necessary to clarify the oncogenic or tumor suppressive role of WT1 in breast cancer.…”
Section: Introductionmentioning
confidence: 97%
“…To explore whether flubendazole induces breast cancer cell differentiation, we performed Oil Red O staining in CS-like cell enriched MDA-MB-231 cells before and after flubendazole treatment (0.125 μM, 3 weeks) [31]. We observed that flubendazole dramatically increased positively staining cells ( p <0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oil-Red-O staining for the detection of lipid droplets was performed as previously described [31]. Images were obtained under microscope.…”
Section: Methodsmentioning
confidence: 99%